Effects of TPMT, NUDT15, and ITPA Genetic Variants on 6-Mercaptopurine Toxicity for Pediatric Patients With Acute Lymphoblastic Leukemia in Yunnan of China - Mao, Xiaoyan; Yin, Runxiu; Sun, Gaoyuan; Zhou, Yan; Yang, Chunhui; Fang, Chunlian; Wu, Yuhong; Cui, Tingting; Liu, Li; Gan, Jiaxin; Tian, Xin (Frontiers in Pediatrics, 2021)
Background: 6-Mercaptopurine (6-MP) is cornerstone of current anti-leukemia regimen and contributes greatly to improve the survival of pediatric acute lymphoblastic leukemia (ALL) patients. However, 6-MP dose-related toxicities limit its application. TPMT, NUDT15 and ITPA are pharmacogenetic markers predicting 6-MP related toxicities, but their genetic polymorphisms differ from ethnic populations. In multi-ethnic region Yunnan province of China, we had no genetic data to predict 6-MP toxicities. In this study, we evaluated the most common variants involved in 6-MP metabolism, TPMT*3C (rs1142345), NUDT15 c.415C > T (rs116855232), and ITPA c.94C > A (rs1127354) variants in our cohort of pediatric ALL patients. Methods: A total of 149 pediatric acute lymphoblastic leukemia (ALL) patients in children’s hospital affiliated to Kunming Medical University (Yunnan children’s Medical Center) from 2017-2019 were enrolled in this retrospective study. We assessed the TPMT*3C (rs1142345), NUDT15 c.415C > T (rs116855232), and ITPA c.94C > A (rs1127354) frequencies and evaluated association between genotypes and 6-MP toxicities, 6-MP dose, event free survival in these ALL patients. Results: The allele frequencies of TPMT*3C (rs1142345), NUDT15 c.415C > T (rs116855232), and ITPA c.94C > A (rs1127354) were 1.34%, 14.43%, and 18.79% respectively. Only NUDT15 c.415C > T (rs116855232) was strongly associated with 6-MP toxicity and 6-MP tolerable dose. NUDT15 c.415C > T was related to Leukopenia, P=0.008, OR=2.743 (95% CI: 1.305-5.768). The T allele was significant correlated with 6-MP tolerable dose, dose of NUDT15 c.415C > T wild genotype CC 39.80+1.32mg/m2, heterozygotes CT 35.20+2.29mg/m2, homozygotes TT 18.95+3.95mg/m2. 6-MP tolerable dose between CC and TT had significant difference, P=0.009. Between CC and CT, CT and TT, they had no significant difference. Event free survival (EFS) showed no significant difference among NUDT15 c.415C > T genotypes. Conclusion: NUDT15 c.415C > T (rs116855232) was an optimal predictor for 6-MP toxicity and tolerable dose in pediatric ALL patients from multi-ethnic region Yunnan province in China and would play an important role in precise therapy for ALL.